2016
DOI: 10.1371/journal.pone.0167210
|View full text |Cite
|
Sign up to set email alerts
|

Association between Alcohol Intake and Hemoglobin A1c in the Korean Adults: The 2011-2013 Korea National Health and Nutrition Examination Survey

Abstract: BackgroundAlthough alcohol consumption is commonly encountered in clinical practice, few studies have investigated the clinical significance of alcohol intake on the use of the hemoglobin A1c (HbA1c) level.ObjectivesThis study was performed to investigate the association between alcohol intake and HbA1c level in the general population.MethodsAmong the 24,594 participants who participated in the 2011–2013 Korea National Health and Nutrition Examination Survey (KNHANES), 12,923 participants were analyzed in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
0
17
1
1
Order By: Relevance
“…The moderate consumption of alcohol is also correlated with a decreased incidence of DM and a decreased incidence of heart diseases in individuals with DM [12][13]. The results of this survey among patients with ESRD showed that the consumption of a moderate amount of alcohol, mostly in the form of wine, is correlated with increased HbA1c levels, and this is in contrast with the survey of Hong et al, who observed that the intake of alcoholic beverages was positively correlated with the drop in HbA1c levels, although in healthy individuals and not in patients with ESRD under hemodialysis [14]. It should be noted, however, that the high consumption of alcohol is linked with the formation of AGEs, insulin resistance, and secondary DM complications since acetaldehyde, one of the main metabolites of alcohol, when in excess, turns into a toxic substance, forming addition compounds with DNA, lipids, and proteins.…”
Section: Discussioncontrasting
confidence: 81%
“…The moderate consumption of alcohol is also correlated with a decreased incidence of DM and a decreased incidence of heart diseases in individuals with DM [12][13]. The results of this survey among patients with ESRD showed that the consumption of a moderate amount of alcohol, mostly in the form of wine, is correlated with increased HbA1c levels, and this is in contrast with the survey of Hong et al, who observed that the intake of alcoholic beverages was positively correlated with the drop in HbA1c levels, although in healthy individuals and not in patients with ESRD under hemodialysis [14]. It should be noted, however, that the high consumption of alcohol is linked with the formation of AGEs, insulin resistance, and secondary DM complications since acetaldehyde, one of the main metabolites of alcohol, when in excess, turns into a toxic substance, forming addition compounds with DNA, lipids, and proteins.…”
Section: Discussioncontrasting
confidence: 81%
“…An increased alcohol intake is often seen in PCT patients. However, the influence of a high alcohol intake on HbA1c is controversial, as studies show that HbA1c may be both decreased and increased by high alcohol consumption …”
Section: Methods To Detect the Level Of Glycemia For The Diagnosis Anmentioning
confidence: 99%
“…As described in detail previously [9,10], a standard drink was defined as a single glass of liquor, wine, or the Korean traditional distilled liquor So-ju. One bottle of beer (355 mL) was counted as 1.6 standard drinks.…”
Section: Methodsmentioning
confidence: 99%
“…One bottle of beer (355 mL) was counted as 1.6 standard drinks. We calculated the amount of alcohol consumed per standard drink to be 10 g, and the average daily alcohol intake was assessed [9,10]. An average consumption of 30 g per day or more, a level of exposure associated with health risks, was considered heavy alcohol drinking [9,1114].…”
Section: Methodsmentioning
confidence: 99%